PENGARUH SERBUK BAN BEKAS SEBAGAI BAHAN TAMBAH PADA CPHMA DENGAN VARIASI SUHU PEMADATAN TERHADAP KARATERISTIK MARSHALL - Indah Handayasari Halim; Irma Sepriyanna (Politeknik Negeri Jakarta, 2022)
Buton asphalt is a kind of natural asphalt found in Indonesia. The government is recently trying to develop various ways so that the use of Buton asphalt can be optimized to meet the demand for quality asphalt supplies for road pavements. CPHMA is a product from the development of Buton asphalt which has the advantage that it can be spread in conditions of air temperature (known as Cold mix) and elevated temperature (known as Hot mix). In this study, tire powder was used in addition to variations of 0%, 2.5%, 7.5% and 12.5% on CPHMA asphalt with variations in compaction temperature of 30oC, 60oC, 90oC, 120oC, and 150oC. Based on the results of tests carried out, the use of used tire powder from motor vehicle waste can improve the performance of CPHMA with an additional percentage of 2.5% at a compaction temperature of 150oC to meet the specified specifications. Keywords: CPHMA, Tire Powder, Marshall.